When Teaching Factories Meet Project-Based Learning: Rethinking Evidence of Impact on Students’ Soft Skills and Entrepreneurial Intention - Verawati, Ni Nyoman Sri Putu; Prayogi, Saiful; Mustofa, Hisbulloh Als (Lensa: Jurnal Kependidikan Fisika, 2025)
This commentary examines Hulyadi et al. (2025), which reports that a project-based teaching factory (PbTF) model in a chemical cleaning industry context improved students’ soft skills and entrepreneurial intention over a short intervention. The article’s key contribution is practical: it operationalizes “teaching factory” as a sequenced learning design with validated tools and measurable outcomes. However, the strength of causal claims is limited by the one-group pretest–posttest design, a small cohort, and outcomes closely aligned with course activities. The observed gains may reflect increased opportunities to collaborate, assessment familiarity, or short-term motivational uplift rather than durable competence and entrepreneurial behavior. This commentary offers a cautious reading of the evidence, proposes alternative interpretations consistent with the reported data, and suggests evaluation steps that would clarify mechanisms, durability, and generalizability. PbTF-PjBL appears promising as an applied learning package, but stronger comparative and longitudinal evidence is needed before treating it as a robust impact model.